Effect of proctor's clinical supervision model on nurses' loyalty in a hospital in Subang, Indonesia - Oktavia, Leli; Minanton, Minanton; Herman, Herman; Jayadi, Alpian (Program Studi Keperawatan, Politeknik Negeri Subang, 2023)
Background: In both personal and professional relationships, loyalty is crucial, and it can affect how we feel about organization we work for. This condition should get the attention of managers, who are directly responsible for the quality of nursing care. Supervision is part of the directing function. Its role is to ensure that all programmed activities are carried out properly and smoothly. Purpose: To determine the effect of proctors' model of clinical supervision on nurses' loyalty in a hospital in Subang. Methods: This research was conducted on nurses at X hospital in Subang using a quantitative research design with a cross-sectional approach. The total sampling was used with a total of 34 respondents. The data were analyzed using simple linear regression. Results: The results showed that the value of α: 8.055, β: 0.964, and the value of T-count: 5.934, with a significance value of 0.002. Clinical supervision of the proctor model has a significant positive effect on nurse loyalty. The magnitude of the effect of clinical supervision under the proctor model on nurse loyalty is 53.2 percent. Conclusion: Clinical supervision under the proctor model has a positive and significant effect on nurse loyalty. Proctor's model in the implementation of clinical supervision can improve nurses’ loyalty and enhance their performance to provide excellent nursing care. An effective supervision model that is successfully and continuously implemented is crucial.